2013
DOI: 10.52131/pjhss.2013.0101.0003
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Determinants of Stock Price Variations: An Economic Analysis of Kse-100 Index

Abstract: The main objective of this study is to assess the macroeconomic determinants of stock price variability in Pakistan. The quarterly data on macroeconomic variables (Gross Domestic Product, Foreign Direct Investment, Interest Rates, Exports, Money Supply and Unemployment Rate) and KSE-100 Index as proxy of stock price variation for the period of 1992:01 to 2012:04 is taken for the empirical investigation. Johansen co-integration test and VECM is used for this purpose. The analysis of this study specifies that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Further, this sign difference can be recognized within the same territory. As an example, Hussain et al (2013) argued a positive relationship and Almutair (2015) argued a negative relationship in Pakistan.…”
Section: Money Supplymentioning
confidence: 99%
“…Further, this sign difference can be recognized within the same territory. As an example, Hussain et al (2013) argued a positive relationship and Almutair (2015) argued a negative relationship in Pakistan.…”
Section: Money Supplymentioning
confidence: 99%
“…This study essentially utilized 10 organizations as test from the oil and gas mining organizations that were recorded on stock trade of Indonesia (IDX) for a time range from 2014-2018, total of fifty numbers of observations. The conclusions of the analysis done by (Hussain, Rafique, Khalil, & Nawaz, 2013;Musallam et al, 2018) demonstrated that nearly a critical impact of institutional ownership, operating leverage, liquidity on worth of the firm on the performance of an organization. Khalfan and Wendt (2020) looked into that how concentration of ownership affects payment policies and the impact of foreign institutions and state as owners on payout by Nordic companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The banks are the central body between the investors and the borrowers, thus, earns a lot of money. If the investors directly done the investment then the cost of investment is greater than the cost which is bearded by the banks, the cost of bank's investment is low because it collects a pool and diversified it in different plans Mantovi (2019)Before making the investment in any stock or security it is obligatory to analyze the risk that is related with this investment (Hussain, Rafique, Khalil, & Nawaz, 2013). For this purpose, the investor pay price for acquiring the information.…”
Section: Introductionmentioning
confidence: 99%